Variabilidad fenotípica y genotípica del germoplasma de cacao nativo Theobroma cacao L. de Loreto 2020 - Imán Correa, Sixto Alfredo (2022)
In the department of Loreto, there is native cocoa in important quantity and quality, but insufficiently studied. INIA has a native cocoa germplasm bank, which lacked phenotypic and genotypic characterization studies. The general objective of this research was to determine the phenotypic and genotypic variability of the native cocoa germplasm Theobroma cacao L.; which includes genetic material collected in the eight provinces of the Loreto region. The phenotypic characterization was carried out in leaves, flowers, fruits and seeds, 38 variables were measured using morphological descriptors. For the genotypic characterization, the genomic DNA of tender leaves was obtained, the libraries were prepared by the double digestion restriction site associated sequencing method (ddRAD-seq) using the Illumina HiSeq 4000 platform. The sequences obtained were analyzed with bioinformatic tools to determine the parameters of genetic diversity. As a result of the phenotypic characterization, a coefficient of variation of 23.05% was obtained, 10 phenetic groups that express high variability. In genotypic characterization, 1,057 single nucleotide polymorphisms (SNPs) were identified, three genetic groups analyzed both by province and by hydrographic basin. The genotypic analyzes indicate that the highest percentage of variation in the genetic diversity of the native cocoa germplasm collection of Loreto Peru (92.05%), is at the level of intrapopulation genetic diversity.